Measuring the Cognitive Domain of the Quality of Student Life: An Instrument for Faculties of Education - Roberts, Lance; Clifton, Rodney (Canadian Journal of Education/Revue canadienne de l’éducation, 1992)
This study presents an instrument for measuring the cognitive domain of the quality of student life in faculties of education, developed using a representative sample of undergraduate and graduate students at a major Canadian university. The findings suggest there are three dimensions of the cognitive domain of the quality of student life: Development of Pupils, Subject Expertise, and the Methodology of Teaching. Alpha reliability coefficients for these scales ranged from 0.72 to 0.75. Cette étude présente un instrument servant à évaluer la facette cognitive de la qualité de la vie étudiante dans les facultés de sciences de l’éducation, instrument mis au point à l’aide d’un échantillon représentatif d’étudiants des premier, deuxième et troisième cycles dans une grande université canadienne. Les conclu- sions semblent indiquer que la facette cognitive de la qualité de la vie étudiante comprend trois dimensions: le développement des étudiants, la maîtrise du sujet d’étude et la méthodologie pédagogique. Les coefficients de fidélité alpha pour ces échelles variaient entre 0,72 et 0,75.